Automorphism of the geometry of the group B_2(2^n) as apolynomial mapping - Peykre, L.R. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
A construction of an automorphism of the geometry of the group B_2(2^n) is given as an extension of an automorphism of a root system. Some properties of the automorphism are proved.